Pelajar Pancasila character development through digital literature in high school - Imas Komala; Ramadiani Ramadiani; Zeni Haryanto (Universitas Pendidikan Indonesia, 2025)
Digital literature, broadly defined as any text consumed on a screen, creates a reading environment that pulses with interactivity. This research presents a systematic review examining the contribution of digital reading materials to the formation of Pancasila character among high school students in Indonesia. The purpose of this study is to investigate whether digital literature can genuinely help high school students grow into more Pancasila-minded citizens. The methodology employed is a qualitative literature review, analyzing empirical, methodologically sound, pertinent, and recent articles published between 2021 and early 2025. Google Scholar served as the primary search hub, utilizing keyword combinations such as